Analysis of Outpatient Patient Satisfaction at Jayagiri Health Center, Lembang Village, West Bandung District - Putri, Meilinda Eka; Hadithya, Riyan (PROMOTOR, 2024)
The success of a company depends on how well its customers remain satisfied when using the products and services offered. Similarly, in the context of healthcare services, a hospital's positive or negative reputation is often determined by the patients' evaluations during inpatient or outpatient care. The method used in this study is a qualitative descriptive method, which aims to understand the phenomena experienced by the research subjects. The study found that the highest value of the satisfaction variable is two and is found in the question "How do you think about the suitability of service requirements with the type of service?" with an average score of 4.07 and "How do you think about the fairness of the cost/fee in the service?" with an average score of 4.07. Additionally, the lowest value is found in the statement "How do you think about the speed of service delivery?" with an average score of 3.17. Therefore, it can be concluded that the patient satisfaction variable in this study can be stated as good, as the average score of this variable is 3.86, which falls into the category of 4 (Good). The conclusion that can be drawn from this study is that patients who receive outpatient care at Jayagiri Health Center are already satisfied with the services provided by the center.